Effects of symbiotic preparations on constipated irritable bowel syndrome symptoms - Dughera, L.; Elia, C.; Navino, et al., M. (Acta Biomedica Atenei Parmensis, 2007)
Background: Prebiotic and probiotic therapies are new strategies that are being used to treat different gastrointestinal diseases, such as irritable bowel syndrome, diverticular disease and inflammatory bowel diseases. Aims: Evaluating the effects of a symbiotic preparation on symptoms and colonic transit in patients with irritable bowel syndrome and significant bloating. Methods:We carried out an open-label, prospective, uncontrolled, multicenter trial on 129 patients meeting Rome II criteria for irritable bowel syndrome who did not have lactose malabsorption, abdominal surgery, overt psychiatric disorders and ongoing psychotropic drug therapy or ethanol abuse. For three months, the patients were treated with a symbiotic preparation and were investigated trough questionnaires on symptoms. Data on bloating and abdominal pain were obtained using the McNemar-Bowker’s test, while data on stool frequency were evaluated using the t-test. Results: The administration of a symbiotic preparation to these patients modified the clinical picture and intestinal function, with a significant increase of stool frequency. Conclusions:Our data, although the study had an open design, represent a further analysis of positive symbiotic effects on clinical manifestations and intestinal function in patients with irritable bowel syndrome.